An Exploration of Collegiate Outdoor Recreation Professionals' Personality Traits and Job Task Affect. Issue 1 (April 2019) - Turnis, Brittany; Jordan, Debra
The present study investigated the Big Five personality traits of 94 collegiate outdoor recreation (COR) professionals employed within a campus recreation setting and examined those in relation to their job satisfaction. An e-mail with a link to an online survey was sent to 233 campus recreation professional members of the Association of Outdoor Recreation and Education. Using the five-factor model (FFM) of personality, the researchers explored the relationship between personality traits (neuroticism, extroversion, openness, agreeableness, and conscientiousness) and level of affect toward common COR program duties (general office, personnel management, interpersonal, and program-specific). Results indicated that COR professionals ascribed the highest level of affect to personnel management tasks followed by interpersonal, program-specific, and then general office tasks. Extroversion was positively correlated with interpersonal job task affect as were agreeableness and openness to experience. Study results suggest that individuals with a higher rating on extroversion would be well suited to work in a COR setting. Such professionals would be creative problem solvers who work well within a group. The overall scoring patterns found indicate that COR professionals are less interested in typical "desk work" as they prefer the fieldwork and interpersonal/social aspects of the job. As interpersonal skills are vital to success in the COR profession, results suggest that when hiring, employers may wish to focus on those applicant traits. Since the necessary organization and administrative tasks are more easily taught to new hires, those skill sets may be taught on the job. To learn about applicant personality traits, employers may wish to integrate a personality assessment into the typical hiring practices to best match new staff with required job skills.